Cancer cachexia and its pathophysiology: links with sarcopenia, anorexia and asthenia. Issue 3 (6th March 2020) - Peixoto da Silva, Sara; Santos, Joana M.O.; Costa e Silva, Maria Paula; Gil da Costa, Rui M.; Medeiros, Rui
Abstract: Cancer cachexia is a multifactorial syndrome characterized by a progressive loss of skeletal muscle mass, along with adipose tissue wasting, systemic inflammation and other metabolic abnormalities leading to functional impairment. Cancer cachexia has long been recognized as a direct cause of complications in cancer patients, reducing quality of life and worsening disease outcomes. Some related conditions, like sarcopenia (age‐related muscle wasting), anorexia (appetite loss) and asthenia (reduced muscular strength and fatigue), share some key features with cancer cachexia, such as weakness and systemic inflammation. Understanding the interplay and the differences between these conditions is critical to advance basic and translational research in this field, improving the accuracy of diagnosis and contributing to finally achieve effective therapies for affected patients.